Altered Vascular Adaptations to Pregnancy in a Rat Model of Advanced Maternal Age - Pasha, Mazhar; Wooldridge, Amy L.; Kirschenman, Raven; Spaans, Floor; Davidge, Sandra T.; Cooke, Christy-Lynn M. (Frontiers in Physiology, 2021)
Advanced maternal age (≥35 years old) increases the risk of pregnancy complications such as preeclampsia and fetal growth restriction. We previously demonstrated vascular dysfunction and abnormal pregnancy outcomes in a rat model of advanced maternal age. However, vascular adaptations to pregnancy in aging were not studied. We hypothesize that advanced maternal age is associated with a more vasoconstrictive phenotype due to reduced nitric oxide (NO) and increased activity of matrix metalloproteinases (MMPs), contributing to impaired vascular adaptations to pregnancy. A rat model of advanced maternal age was used: young (4 months) and aged (9.5 months; ∼35 years in humans) non-pregnant and pregnant rats. On gestational day 20 (term = 22 days; non-pregnant rats were aged-matched), blood pressure and heart rate were measured (tail cuff plethysmography) and vascular function was assessed in mesenteric arteries (wire myography). Endothelium-dependent relaxation to methylcholine (MCh) was assessed in the presence/absence of nitric oxide synthase inhibitor (L-NAME), or inhibitors of endothelium-dependent hyperpolarization (EDH; apamin and TRAM-34). Vasoconstriction responses to big endothelin-1 (bigET-1), in the presence/absence of MMPs-inhibitor (GM6001) or endothelin converting enzyme (ECE-1) inhibitor (CGS35066), in addition, ET-1 responsiveness, were measured. Blood pressure was elevated only in aged non-pregnant rats (p < 0.001) compared to all other groups. MCh responses were not different, however, L-NAME decreased maximum vasodilation in young (p < 0.01) and aged pregnant rats (p < 0.001), and decreased MCh sensitivity in young non-pregnant rats (p < 0.01), without effects in aged non-pregnant rats. EDH contribution to relaxation was similar in young non-pregnant, and aged non-pregnant and pregnant rats, while EDH-mediated relaxation was absent in young pregnant rats (p < 0.001). BigET-1 responses were enhanced in aged non-pregnant (p < 0.01) and pregnant rats (p < 0.05). No significant changes in bigET-1 conversion occurred in the presence of MMP-inhibitor, whereas ECE-1 inhibition reduced bigET-1 constriction in aged rats (p < 0.01). No differences in ET-1 sensitivity were observed. In conclusion, contrary to our hypothesis, reduced blood pressure, and an increased EDH-dependent contribution to vasodilation suggest a compensatory mechanism that may reflect beneficial adaptations in these aged rats that were able to maintain pregnancy. These data increase our understanding of how the vascular adaptive pathways in pregnancy compensate for advanced maternal age.